Perspectives from Hmong-American women about the first-generation college student experience in higher education. Issue 6 (1st November 2020) - Ducklow, Lacey; Toft, Jessica
ABSTRACT: While the research regarding Hmong-American women as first-generation college students (FGCS) has grown, it emphasizes cultural and individual factors, neglecting institutional and systemic factors that may mediate academic success. Using an ethnographic and phenomenological approach, interviews were conducted with six female Hmong-American FGCS to address the following question: What factors promote and impede success in higher education? Applying grounded theory data analysis method, four categories of themes emerged: complex culture clash, higher education institution experience, supports for success, and changing view of higher education. Future research is recommended regarding the interface and impact of specific aspects of education, as well as a needed focus on male students' experiences.